Correction: Total saponins from Rosa laevigata Michx fruit attenuates hepatic steatosis induced by high-fat diet in rats. Issue 8 (6th August 2019) - Dong, Deshi; Qi, Yan; Xu, Lina; Yin, Lianhong; Xu, Youwei; Han, Xu; Zhao, Yanyan; Peng, Jinyong
Abstract : Correction for 'Total saponins from Rosa laevigata Michx fruit attenuates hepatic steatosis induced by high-fat diet in rats' by Deshi Dong, et al., Food Funct., 2014, 5, 3065–3075.